Modelling an emergency vehicle early-warning system using real-time feedback. (15th May 2008) - Senart, Aline; Bouroche, Melanie; Cahill, Vinny
Emergency vehicles, while usually equipped with warning devices, are still often impeded by other traffic and involved in numerous collisions. Current research is investigating the use of wireless communication from emergency vehicles to warn other traffic. However, communication in dynamic wireless networks is not reliable. In this paper, we propose a novel emergency vehicle early-warning system that relies on wireless technology to inform other vehicles of the arrival of emergency vehicles, and returns feedback in real-time when communication degrades. We describe how such a system is built with Comhordu, a coordination model for wireless networks.